Multiple case study analysis on the consequences of mandatory sustainability reporting in private German family firms - Ralf Ebner (Junior Management Science (JUMS), 2024)
This study explores the consequences of the Corporate Social Responsibility Reporting Directive (CSRD) on family firms. The European Commission (EC) extends under the CSRD the number of reporting companies from approximately 12,000 to 50,000, with the greatest increase in Germany. For 2025, around 13,000 German private family firms must disclose a sustainability report for the first time. Preparing a sustainability report that meets the requirements of the CSRD involves its own consequences. Based on a multiple case study of ten private German family firms, I develop a framework that illustrates implementation challenges and provides guidance to unlock business opportunities. Building on family business research, I contribute to the literature by differentiating family firms based on their sustainability strategy and maturity of sustainability reporting. This allows us to derive three archetypes facing varying implementation challenges. The analysis reveals direct and indirect opportunities along a firm's value chain. After introducing a reporting process, all archetypes can benefit from direct opportunities, whereas a proactive sustainability strategy needs to unlock indirect opportunities.
Keywords: 330; corporate sustainability; corporate sustainability reporting directive; family firms; mandatory sustainability reporting; socioemotional wealth